Shaming, Shame and Recidivism - Murphy, Kristina (The British journal of criminology, 2007)
Despite the popularity of reintegrative shaming theory in the field of criminology, only a small number of studies purporting to test it have been published to date. The aim of the present study, therefore, is to provide an empirical test of Braithwaite's (1989; Braithwaite and Braithwaite 2001) theory of reintegrative shaming in the white-collar crime context. The data on which the study is based came from survey data collected from a group of 652 tax offenders. Consistent with predictions, it was found that feelings of reintegration/stigmatization experienced during an enforcement event were related to reoffending behaviour. Those taxpayers who felt that their enforcement experience had been reintegrative in nature were less likely to report having evaded their taxes two years later. Consistent with Braithwaite and Braithwaite's (2001) hypotheses, shame-related emotions were also found to partially mediate the effect of reintegration on subsequent offending behaviour. Implications for the effective regulation of white-collar offenders are discussed